2000
DOI: 10.1021/ef000069s
|View full text |Cite
|
Sign up to set email alerts
|

Surfactants as Hydrate Promoters?

Abstract: Natural gas hydrates from different types and concentrations of surfactant solutions were produced in a high-pressure cell. An anionic, a cationic, and a nonionic surfactant were used to prepare different concentration of surfactant solutions from deionized water. Although the thermodynamics of hydrate formation from a gas mixture is not affected with the existence of surfactants in the environment, there is an appreciable effect of type and concentration of surfactant on hydrate formation rate. The hydrate fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(118 citation statements)
references
References 7 publications
5
112
0
Order By: Relevance
“…Their study (Gudmundsson and Brrehaug, 1996) also showed a substantial cost saving (24%) for the transport of natural gas in hydrates compared to liquefied natural gas from the northern North Sea to Central Europe. The hydrate formation with promoters for the purpose of natural gas storage and transport has been reported recently (Saito et al, 1996;Khokhar et al, 1998;Karaaslan and Parlaktuna, 2000;Zhong and Rogers, 2000;Guo et al, 2002). But prior to industrial applications of hydrate storage processes were used, some problems, such as slow formation rates, unreacted interstitial water as a large percentage of hydrate mass, the reliability of hydrate storage capacity and economy of process scale-up, must be solved.…”
Section: Introductionmentioning
confidence: 95%
“…Their study (Gudmundsson and Brrehaug, 1996) also showed a substantial cost saving (24%) for the transport of natural gas in hydrates compared to liquefied natural gas from the northern North Sea to Central Europe. The hydrate formation with promoters for the purpose of natural gas storage and transport has been reported recently (Saito et al, 1996;Khokhar et al, 1998;Karaaslan and Parlaktuna, 2000;Zhong and Rogers, 2000;Guo et al, 2002). But prior to industrial applications of hydrate storage processes were used, some problems, such as slow formation rates, unreacted interstitial water as a large percentage of hydrate mass, the reliability of hydrate storage capacity and economy of process scale-up, must be solved.…”
Section: Introductionmentioning
confidence: 95%
“…Surfactants do not change the thermodynamics of clathrate hydrates, but they have been found to alter clathrate hydrate kinetics. Karaaslan and Parlaktuna [58] have found that anionic surfactants increase hydrate formation rate at all concentration, cationic surfactants increase hydrate formation rate at low concentration, and nonionic surfactants have little distinguishable effects on hydrate formation rate. SDS is a commonly used surfactant that is known to increase hydrate stability.…”
Section: Promotersmentioning
confidence: 99%
“…Based on the chemical structures, three anionic, cationic and non-ionic surfactants with the commercial name of LABSA, Dehyguard Dam (DAM) and Ethoxalate have been examined for their effect on the formation kinetics of gas hydrate and their ability as hydrate promoter (Karaaslan and Parlaktuna, 2000). It was found that the overall hydrate formation rate was increased with the use of anionic surfactant for all concentrations tested.…”
Section: Surfactantsmentioning
confidence: 99%